PENGELOLAAN ARSIP SEBAGAI SUMBER INFORMASI BAGI SUATU ORGANISASI MELALUI ARSIP MANUAL DAN ARSIP DIGITAL - Husnita, Tri Jely; Kesuma, Mezan el-Khaeri (Jurnal El-Pustaka, 2020)
In the era of information technology and digital, the government or private institution carries out an activity for an organization. These activities include the creation and creation, storage, recording, and destruction of archives. An archive is processed and created and stored to be more effective and efficient. To perform archive management consists of two functions, namely static and dynamic archives, each of which has an important role in success in managing records. The archive aims to facilitate the search for documents for the required period. In the era of globalization, archives are divided into two parts, namely manual archives and digital archives. To manage records in an organization it is divided into three parts, namely centralization, decentralization, and a combination of centralization and decentralization. So with the existence of a digital era, there have been many changes in the formulation of an archive policy.